-11=11(h-2)

Simple and best practice solution for -11=11(h-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -11=11(h-2) equation:


Simplifying
-11 = 11(h + -2)

Reorder the terms:
-11 = 11(-2 + h)
-11 = (-2 * 11 + h * 11)
-11 = (-22 + 11h)

Solving
-11 = -22 + 11h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-11h' to each side of the equation.
-11 + -11h = -22 + 11h + -11h

Combine like terms: 11h + -11h = 0
-11 + -11h = -22 + 0
-11 + -11h = -22

Add '11' to each side of the equation.
-11 + 11 + -11h = -22 + 11

Combine like terms: -11 + 11 = 0
0 + -11h = -22 + 11
-11h = -22 + 11

Combine like terms: -22 + 11 = -11
-11h = -11

Divide each side by '-11'.
h = 1

Simplifying
h = 1

See similar equations:

| 1.6(6-v)=10 | | 2x-10=6x-18 | | (7x-8)+(3x+8)=180 | | -x+4=17 | | 2y-9=-23 | | 7.5+2.2n=-5.6 | | (x+5)=49 | | -9(t+2)=0 | | 2x+52=8x-14 | | 14x-7=5+11x | | 17=5q+2 | | -14=3.1(k-4) | | 10+3x=30+4x | | 1-x+6=16 | | 70-6x=39x+20 | | (x-5)(3x-6)=0 | | 5-(4x-5)=-25x-30 | | 2.8(m-5)=-20 | | d=ab^2c+1 | | 7x^2+28x+3=0 | | 18p+=11-3p | | x-x-20=0 | | 2x+(4x+16)=7 | | 3(w-3)=18 | | 8.2=1.9f-2.6 | | 6x^2=168 | | 1.5(3+x)=6.5 | | 7x+2=5x+9 | | 3x-(6-12x)=4(3-15x) | | X^2-6x-216=0 | | 3-4x=-5+8x | | -5(t-8)-(t+7)=7 |

Equations solver categories